# Calculus

posted by Mina

solve second-order initial value problem

y"(x)= x e^-2x
y'(0)= 0
y(0)= 0

1. drwls

First you need to integrate y"(x). This looks like a situation where "integration by parts" can be used.
Let u(v) = x and dv = e^-2x dx
du = dx v = (-1/2)*e^-2x
Integral of u dv = uv - integral of v du
= (-x/2)e(-2x) + Integral of(1/2)*e^-2x dx
Finish that off and use the y'(0) = 0 condition to solve for the arbitary constant. Once you have dy/dx, integrate again and use the initial condition at y(0) for the y(x) solution.

## Similar Questions

1. ### Calculus - Second Order Differential Equations

Solve the boundary-value problem. y''+5y'-6y=0, y(0)=0, y(2)=1 r^2+5r-6=0, r1=1, r2=-6 y=c1*e^x + c2*e^-6x y(x)=c1*e^x+c2*e^-6x y'(x)=c1*e^x-6*c2*e^-6x y(0)=c1+c2=0, c1=-c2 y(2)=c1*e^2+c2*e^(-12)=1 -c2*e^2-6c2*e^(-12)=1 -c2(e^2-6*e^-12)=1 …
2. ### Calculus - Second Order Differential Equations

Solve the initial-value problem. y'' - 2y' + y = 0 , y(2) = 0 , y'(2) = 1 r^2-2r+1=0, r1=r2=1 y(x)=c1*e^x+c2*x*e^x y(2)=c1*e^2+c2*2*e^2=0 c1=-(2*c2*exp(2))/exp(2) c1=-2*c2 y'(x)=-2*c2*e^x+c2*e^x*(x-1) y'(2)=-2*c2*e^2+c2*e^2*(2-1)=1 …
3. ### Calculus

Solve the first-order initial value problem using half angle formulas {y'(x)= 1 + sin^2 x y (0)= -7
4. ### calculus

How do you solve the initial value problem?
5. ### Calculus

Solve the following initial value problem explicitly: y'= ye^-x , y(0)=1 How do you solve this problem?
6. ### Calculus

Solve the initial-value problem. y'' - 2y' + y = 0 , y(2) = 0 , y'(2) = 1
7. ### calculus

Hello! Just needed help with understanding this specific question. We never really wet over Euler's method so I'm not sure how to go about it. "Use Euler's method in order to solve the initial value problem below. dy/dx = x-3 and y=4 …
8. ### Help! Calculus

I am so confused on how to solve this problem. I have it set up with y's on one side and x's on the other but I don't know what to do from there. Question: Solve the differential equation. The initial condition is y(0) = 1. ((x^2+1)^(1/2))(dy/dx) …
9. ### Calculus

Solve the initial value problem. dy/dx = 3 sinx and y = 2 when x = 0. Is this c = 5?
10. ### Calculus

Solve the initial value problem. 7x^6-3x^2+5 and u = 1 when x = 1. Is this x^7 - x^3 + 5x - 4?

More Similar Questions